Artificial Intelligence and two translations from Macedonian to Polish (Slavic Studies, 2024)
: In this article we analyze the translation from Macedonian to Polish of a poem "The Fifth Prayer of My Body" by Aco Shopov, translated by the Artificial Intelligence.
Keywords: Artificial Intelligence; translation; Macedonian; Polish language